Response of grapevine cv. 'Tempranillo' to timing and amount of irrigation: water relations, vine growth, yield and berry and wine composition - Intrigliolo, Diego S.; Castel, Juan R. (2017)
The effects of several moderate irrigation regimes on vine water status, yield, and must and wine composition, were investigated during five seasons in a vineyard planted with Vitis vinifera cv. Tempranillo. Treatments consisted of non-irrigated vines and six differentially irrigated treatments with contrasting watering regimes during the pre-veraison and post-veraison periods. There were large differences in yield and grape and wine quality responses to irrigation among seasons, probably as consequence of the different environmental conditions and crop levels. It was, however, clear that vines benefit more of the irrigation supplied in years of high yield levels. Across seasons, yield increased in proportion to the amount of water applied mostly due to the larger berries of irrigated vines, and there was no clear response to the timing of irrigation supplied. In addition, there were no carry over effects due to irrigation on bud fertility. The post-veraison water application was necessary to increase must sugar level and wine alcohol content. However, water restrictions during the pre-veraison period lead to more concentrated berries in terms of total phenolic and anthocyanins. The only noticeable detrimental effect of irrigation, regardless of the timing of its application, on wine composition was an increase in wine pH.